Dual-time-resolution pulse-position modulator for time-based serial communication links. Issue 4 (1st October 2016) - Rashdan, Mostafa; Haslett, James W.
ABSTRACT: A dual-time-resolution pulse-position modulator (DTR-PPM) that combines a high-time-resolution PPM circuit with a conventional PPM circuit is described. The DTR-PPM circuit can be used in time-based serial links to increase the number of modulated bits without significantly affecting the modulated signal bandwidth. It also reduces the number of bits of the required time-to-digital converter (TDC) circuits that are used at the receiver side. The design details of the receiver circuit for the proposed dual-time-resolution transmitter are also presented. An example 4-bit 6.4 Gb/s DTR-PPM incorporating the high-time-resolution PPM is simulated in 65 nm CMOS. The proposed DTR-PPM circuit consumes 230 µW.